Gender Anthropology in the Middle East: The Politics of Muslim Women’s Misrepresentation (American Journal of Islam and Society, 1991)
The Western view of the role of women in Muslim societies presentsa strikingly ambivalent attitude. On the one hand, the patrilineal, patriarchalstructure of the Muslim family has been so emphasized that it is believedto be at the heart of the assumed subordination of women in Muslim societies(Rassam 1983; Joseph 1985). On the other hand, a matrilineal structure isbelieved to exist in at least some Muslim societies. Frantz Fanon speaks ofhow the French colonizers of Algeria developed a policy built on the“discoveries” of the sociologists that a structure of matriarchal essence didindeed exist. These findings enabled the French to define their politicaldoctrine, summed up by Fanon as: “If we want to destroy the structure ofAlgerian society, its capacity for resistance, we must first of all conquer thewomen, we must go and find them behind the veil where they hide themselves,and in the houses where the men keep them out of sight” (Fanon 1965, 39).France’s success or failure in adopting this policy, and the repercussionsof the adoption of this formula, are beyond the scope of this paper. Whatis important here is its implication vis-\a-vis the importance of women. Also,it enables us to be cognizant of a structured irony in the politics of studyingMuslim women, whether for practical colonial purposes, or for intellectualorientalist aims. In the case of women, for example, French colonialists triedto use them to destroy the structure of Algerian society by attributing to theman almost absolute “significance.” On the other hand, orientalists have usedMuslim women also, but with the aim of destroying the image of Islam byrendering them absolutely “insignificant” within the religion.The view of Islam as a purgatory for women underlies most works writtenon Muslim women. They are commonly depicted as isolated from men, passiveactors in the so-called public domain, confined to their kin groups, and so ...